The role of tripartite motif-containing 28 in cancer progression and its therapeutic potentials - Yang, Yiqing; Tan, Shiming; Han, Yaqian; Huang, Lisheng; Yang, Ruiqian; Hu, Zifan; Tao, Yi; Oyang, Linda; Lin, Jinguan; Peng, Qiu; Jiang, Xianjie; Xu, Xuemeng; et al. (Frontiers in Oncology, 2023)
Tripartite motif-containing 28 (TRIM28) belongs to tripartite motif (TRIM) family. TRIM28 not only binds and degrades its downstream target, but also acts as a transcription co-factor to inhibit gene expression. More and more studies have shown that TRIM28 plays a vital role in tumor genesis and progression. Here, we reviewed the role of TRIM28 in tumor proliferation, migration, invasion and cell death. Moreover, we also summarized the important role of TRIM28 in tumor stemness sustainability and immune regulation. Because of the importance of TRIM28 in tumors, TIRM28 may be a candidate target for anti-tumor therapy and play an important role in tumor diagnosis and treatment in the future.